I am right you are wrong : from this to the new Renaissance : from rock logic to water logic - De Bono, Edward (UK : Penguin Life, 2016)
Most of our everyday decision-making tends to be confrontational. Whether in large meetings, one-to-one or even in our own heads, opposite view points are pitted against each other. This title challenges this 'rock logic' of rigid categories and point-scoring arguments which is both destructive and exhausting.
Keywords: Thought and thinking; Decision making; Logic